Beta-adrenergic blocking agents in cutaneous and oral melanoma - Sivakamavalli Jeyachandran (Oral Oncology Reports)
Beta-adrenergic blocking agents, or beta-blockers, are primarily used to manage cardiovascular conditions such as hypertension, heart failure, and arrhythmias by blocking the effects of stress hormones on beta-adrenergic receptors, reducing heart rate and blood pressure. Recent research highlights their potential impact on cancer, including cutaneous and oral melanoma. Beta-adrenergic receptors, present on various cell types including tumor cells, influence cancer processes like cell proliferation, angiogenesis, metastasis, and immune response modulation. In melanoma, beta-blockers may alter the tumor microenvironment, affecting cancer progression and treatment outcomes. Studies suggest beta-blockers might reduce cutaneous melanoma progression by inhibiting angiogenesis and tumor cell proliferation, improving survival rates. In oral melanoma, beta-blockers may disrupt stress-induced signaling pathways, reducing tumor growth and metastasis while modulating immune responses. This emerging research indicates beta-blockers' potential as adjunct therapy in melanoma treatment, necessitating comprehensive clinical studies to confirm their efficacy and safety. Future investigations should focus on large-scale trials, exploring the effects of different beta-blockers, and their combination with existing therapies. Beta-blockers show promise in melanoma therapy, offering hope for improved patient outcomes in this challenging disease.